Description of the Al-Qur'an Mushaf Memorizing Aeen - Herliani Herliani (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2025)
One of the three standard mushafs of reference of the Lajnah is the Standard Mushaf of Bahriyah. Mushaf which refers to Turkish mushaf is widely used by memorizers of the Qur'an. Among its features is that physically each page consists of 15 lines, each juz contains 20 pages, and verses always end on each page which makes it easy to divide the stages of memorization. Nowadays along with the increasing enthusiasm of people to memorize, activists modify the physical appearance and affix. Nowadays along with the increasing enthusiasm of people to memorize, activists modify the physical appearance and affix methods to make it more attractive. One of them is a mushaf called the AKMAL version of the AEEN Qur'an which has printed more than 20,000 mushafs. This search is to examine the description of the mushaf from the textual side, as well as contextually. This search is to examine the description of the mushaf from the textual side, as well as contextually. The textual Qur'an memorization of AEEN shows modern mushaf. In addition to being taṣḥīḥ Lajnah in 2021, the illumination is simple and prioritizes functions, namely tilawah, tahfiz, and murajaah, so that how to use the TES method is important and interesting additional content. The mushaf initiated by Bang Jemmi Gumilar has spawned many huffaz ranging from children to adults with various professions. Printed more than 20,000 exp in its young age, this mushaf inscribed gold ink on the history of the development of modern mushaf.